Skeletal metastasis from a squamous cell carcinoma of the nictitating membrane in a Haflinger horse. (3rd October 2019) - de Preux, M.; Gurtner, C.; Klebic, I.; Waschk, M. A.; Drögemüller, C.; Brünisholz, H. P.
Summary: A 12‐year‐old Haflinger gelding with a history of a persistent cough was referred for evaluation of a severe lameness of the left forelimb. An excision of the right nictitans had been performed 2 years prior to presentation, and a squamous cell carcinoma (SCC) with embolic neoplastic cells in several blood vessels had been confirmed by histopathology. The origin of the lameness could not be localised with regional analgesia; therefore, a nuclear scintigraphic examination was performed. This revealed an area of marked increased radiopharmaceutical uptake at the level of the caudodorsal border of the left scapula. Further examination, including ultrasound‐guided biopsy of the suspect region, confirmed the presence of SCC invading the scapula. Due to poor a prognosis, the horse was subjected to euthanasia. Prior to euthanasia, the gelding was tested homozygous for the missense variant in the damage‐specific DNA‐binding protein 2 ( DDB2 ) gene, which is reported as a risk factor for the development of nictitans SCC in Haflinger horses. Post‐mortem evaluation revealed multiple SCC metastasis, affecting the scapula, the liver and the lungs. To the authors' knowledge, this is the first reported case of bone metastasis following a primary periocular SCC in a horse.